101 things i learned in culinary school - Louis Eguaras; Matthew Frederick (New York : Crown, 2020)
"An informative, illustrated guide to food, cooking, and the culinary profession by a former White House chef. A chef must master countless techniques, memorize a mountain of information, and maintain a zenmaster's calm. This book illuminates the path to becoming a culinary professional by sharing important kitchen fundamentals and indispensable advice"-- Provided by publisher
Keywords: Cooking Study and teaching; Cuisiniers Formation